2017
DOI: 10.1016/j.jmbbm.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of bovine intervertebral discs across strain rates

Abstract: The intervertebral disc (IVD) is a complex structure responsible for distributing compressive loading to adjacent vertebrae and allowing the vertebral column to bend and twist. To study the mechanical behaviour of individual components of the IVD, it is common for specimens to be dissected away from their surrounding tissues for mechanical testing. However, disrupting the continuity of the IVD to obtain material properties of each component separately may result in erroneous values. In this study, an inverse f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 30 publications
6
35
0
Order By: Relevance
“…Given the calibration of the annulus in tension, the nonlinear behaviour of the fibres is more prominent to the specimen behaviour, resulting in a ratio k 1 / k 2 lower than those reported here. Other studies that performed direct-controlled calibration of intervertebral disc behaviour for more than one specimen either assumed axial symmetry of bovine discs and relatively low axial compressive strains [ 8 ] or used a relatively low numbers of human discs (three) for a large number of unknowns (six parameters, varying with the degree of degeneration of each disc) [ 4 ]. For bovine discs, the axial symmetry is a relatively weak assumption, with the endplates showing different concavity in the proximal and distal sides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the calibration of the annulus in tension, the nonlinear behaviour of the fibres is more prominent to the specimen behaviour, resulting in a ratio k 1 / k 2 lower than those reported here. Other studies that performed direct-controlled calibration of intervertebral disc behaviour for more than one specimen either assumed axial symmetry of bovine discs and relatively low axial compressive strains [ 8 ] or used a relatively low numbers of human discs (three) for a large number of unknowns (six parameters, varying with the degree of degeneration of each disc) [ 4 ]. For bovine discs, the axial symmetry is a relatively weak assumption, with the endplates showing different concavity in the proximal and distal sides.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at larger strain levels, several of the assumptions in Newell et al . [ 8 ], such as linearity of the fibres or rigidity of the bone, are no longer valid. Previous work validating finite-element models of functional spinal units had shown that nonlinear material models were required at axial compression higher than 15% apparent strains [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further point to highlight with respect to the dynamic simulations is that bone cement and polyoxymethylene specimen holders were defined as rigid bodies [ 60 ]. As the rigid body constraints were set at the centres of mass of the objects, the reaction forces from the caudal constraints were not available for these simulations; therefore, experimental load data from the bottom load cell were used to produce load-displacement curves.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, under mechanical loading, the fluid, flowed out, leads to chemical imbalances that generate fluid inflow [1,2]. The time-dependent response of the disc tissues is largely governed by the interactions between the inelastic features of the tangled ECM (representing all non-fibrillar "solid" components) and the surrounding physiological fluid by osmotic effect [3][4][5][6][7][8][9][10][11]. The resulting chemo-mechanical couplings in the disc tissues are now well accepted but not fully understood [12,13] and corresponding data are rare in the literature.…”
Section: Introductionmentioning
confidence: 99%